Do oral para o escrito na escola: uma forma de ensinar a compreender dois sistemas de expressão da Língua Portuguesa - Ariadine Zacarias de Sousa (2019)
This research work is based on the fact that, in the written productions created by the students of regular classes of the final years of Elementary School, for Portuguese language classes, it is frequent to transcribe parts of everyday speech in texts that should be written in norm standard of the language. The orality marks can be called Conversational Markers - MC's. Although the literature generally defines the MCs as prosodic resources used to maintain the interaction between the interlocutors during speech, denominated by prosodic knots - Level 1 (stretches / emphases, pauses, changes in pitch, speech rate , truncations), we are proposing that MCs can also be: a) Lexical: phoric ("look", "this" ...), deictics of time ("now", "already" ("Here", "hence", ...), summary or explanatory words ("thus", "that neither"); b) Non-Lexical: filler expressions ("humm", "éh :: ...", "ã" ...), abstracters ("tátátá", parará-parará...); c) Pho-nological-Phonological - Prosodic Level 2 (monotongations, diphthongations, degeminations, haplologies, prosthetics, epinetheses, elisions, syncopes, apócopes, apheresis ...); d) Pragmatics: beginnings of conversation ("there," "okay", "let's go?" ...), requests for support ("is not it?", "right?") ("Okay", "there", "other thing" ...); e) Morphosyntactic: inadequate gender con-cordances, inadequate number agreement, inadequate person agreement, inadequate time / mode concordances, unfinished sentences, inadequate regencies. It is common for oral lan-guage to interfere in the written language of the subjects and, therefore, the school should assist the student in the process of oral / written transformation, without labeling one modality or another as "correct" or better, but emphasizing the use considering the linguistic variations and the processes involved in their uses. In this way, a pedagogical intervention project was developed and applied aimed at improving the capacity to retextualize the discursive genre of lived experience, from the oral modality to the written modality. The focus was centered on the process of textualization that involves each of these modalities and their social uses. The place of application of the research work was the State School Professor Clóvis Salgado, lo-cated in the city of Belo Horizonte, in a regular class of the 9th year of Elementary School. The main activities were: audio recording of oral reports of lived experience of the students, followed by faithful transcriptions of these reports; identification, classification, analysis and counting (frequency) of Conversational Markers; retextualization of oral texts in written texts, in formal language. As a result, students understood better the characteristics of the oral and written systems of the Portuguese Language, learning to adapt their productions according to social uses.